1981
DOI: 10.1007/bf00131240
|View full text |Cite
|
Sign up to set email alerts
|

Specialization in the behaviour of chromosomes on the meiotic spindle

Abstract: The kinetic activity of chromosomes is either distributed evenly along the length of the chromosome or localized in a single centromere. Within the group of organisms with evenly distributed (holokinetic) activity great variation occurs, which has its consequences for chromatid segregation. Three major types, with some overlap, can be distinguished. They form a gradient of increasing specialization. Arguments are presented for the hypothesis that the monokinetic chromosomes are nothing but the end point in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Several authors (e.g. VAARMA 1954;HUGHES-SCHRADER and ScHRADER 1961;SYBENGA 1981;WRENSCH et al 1994) suggested that «primitive» bolocentric chromosomes have given rise to monocentric chromosomes. We assume 1987FEINBRUN-DOTHAN 1978FINN 1937FINN 1937VASEDU-VAN 1975FINN 1937VASEDU-VAN 1975P AZY and PLITMANN 1991PAZY and Pr.rrMANN 1991VASUDEVAN 1975FINN 1937present study VASUDEVAN 1975FINN 1937VASUDEVAN 1975KAUL and BHAN 1977SHARMA and CHAT-TERJI 1957KAUL and BHAN 1977 like some other authors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (e.g. VAARMA 1954;HUGHES-SCHRADER and ScHRADER 1961;SYBENGA 1981;WRENSCH et al 1994) suggested that «primitive» bolocentric chromosomes have given rise to monocentric chromosomes. We assume 1987FEINBRUN-DOTHAN 1978FINN 1937FINN 1937VASEDU-VAN 1975FINN 1937VASEDU-VAN 1975P AZY and PLITMANN 1991PAZY and Pr.rrMANN 1991VASUDEVAN 1975FINN 1937present study VASUDEVAN 1975FINN 1937VASUDEVAN 1975KAUL and BHAN 1977SHARMA and CHAT-TERJI 1957KAUL and BHAN 1977 like some other authors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Within a given karyotype, the holocentric chromosomes often display variable behaviour during meiosis (Sybenga 1981). Our study confirmed the different behaviour of sex chromosomes and autosomes in meiosis of Dysdera crocata.…”
Section: Modifications Of Meiotic Divisionmentioning
confidence: 98%
“…The latter phenomenon, i.e., equatorial division preceding the reductional division, was referred to as "inverted meiosis" (e.g., Cope and Stace 1985). Other terms connected with it were postreductional meiosis and autotellic and amphitellic orientation of sister chromatids in meiosis (e.g., Rieger et al 1968;Sybenga 1981). It has been reported in insects (e.g., in coccids (Hughes-Schrader 1948)) and in a few plant families:…”
Section: Introductionmentioning
confidence: 98%